Manoyl Oxide (13R), the Biosynthetic Precursor of Forskolin, Is Synthesized in Specialized Root Cork Cells in Coleus forskohlii . Issue 3 (30th January 2014) - Pateraki, Irini; Andersen-Ranberg, Johan; Hamberger, Britta; Heskes, Allison Maree; Martens, Helle Juel; Zerbe, Philipp; Bach, Søren Spanner; Møller, Birger Lindberg; Bohlmann, Jörg; Hamberger, Björn
Abstract : The first two steps of the biosynthesis of forskolin are active in Coleus forskohlii root cork cells harboring hydrophobic intracellular compartments used for terpenoid storage . Abstract: Forskolin, a complex labdane diterpenoid found in the root of Coleus forskohlii (Lamiaceae), has received attention for its broad range of pharmacological activities, yet the biosynthesis has not been elucidated. We detected forskolin in the root cork of C. forskohlii in a specialized cell type containing characteristic structures with histochemical properties consistent with oil bodies. Organelle purification and chemical analysis confirmed the localization of forskolin and of its simplest diterpene precursor backbone, (13R) manoyl oxide, to the oil bodies. The labdane diterpene backbone is typically synthesized by two successive reactions catalyzed by two distinct classes of diterpene synthases. We have recently described the identification of a small gene family of diterpene synthase candidates (CfTPSs) in C. forskohlii . Here, we report the functional characterization of four CfTPSs using in vitro and in planta assays. CfTPS2, which synthesizes the intermediate copal-8-ol diphosphate, in combination with CfTPS3 resulted in the stereospecific formation of (13R) manoyl oxide, while the combination of CfTPS1 and CfTPS3 or CfTPS4 led to formation of miltiradiene, precursor of abietane diterpenoids in C. forskohlii . Expression profiling and phylogenetic analysis of the CfTPS family further support the functional diversification and distinct roles of the individual diterpene synthases and the involvement of CfTPS1 to CfTPS4 in specialized metabolism and of CfTPS14 and CfTPS15 in general metabolism. Our findings pave the way toward the discovery of the remaining components of the pathway to forskolin, likely localized in this specialized cell type, and support a role of oil bodies as storage organelles for lipophilic bioactive metabolites.